WHOS THE PROFAE STUDENT? - Maria Mercedes Loureiro Escuder; Maria de Lourdes Zanin; Ana Aparecida Sanches Bersusa (Universidade Federal de Goias, 2004)
The main objective of this study was to describe the profile of students from the Ipiranga Hospital,studying the technical course named Project for Capacitating as Professionals the Nursing Area Workers, orPROFAE, linked to the Training Center of Human Resources (CEFOR) of the Health Secretariat of the State of SoPaulo. Two questionnaires were applied, one at the beginning of the course, with 36 responses, and the other inthe end, with 30 responses. Six students abandoned the course. Besides the personal and professionalinformation, the subjects were asked about their expectations of professional changes (improvement of knowledge,in the quality of their work, of wage and satisfaction) measured in scales from 1 to 10. The analysis showed thatstudents were in average 40 years old, and lived nearby. The majority had become nursing assistants in privateschools, from 1994 to 1997. Their professional experience was attained in clinical wards, intensive care units andEmergency Rooms, and they were currently responsible for giving medicine, dressing wounds, and verifying vitalsigns and hygienic.The students reported positive changes for the quality of their work, their satisfaction and knowledge, in thebeginning as well as at the end of the course; as for their wage, the initial positive expectation was inverted by theend of the course, when the students realized how little it would change. Most of the students had positive changesin their practice, as reported by the R.N. nurses of their workplace, but this did not imply in a promotion. In regard tothe meaning of the course for themselves, most believed they had become professionally updated and that thecourse was of good quality. The results of this study may be important to subsidize the organizers of teacherstraining, as well as course coordinators, about technical nurses qualification.